2005
DOI: 10.1002/jmr.724
|View full text |Cite
|
Sign up to set email alerts
|

The structural basis of recognition and removal of cellular mRNA 7-methyl G ?caps? by a viral capsid protein: a unique viral response to host defense

Abstract: The single segment, double-stranded RNA genome of the L-A virus (L-A) of yeast encodes two proteins: the major coat protein Gag (76 kDa) and the Gag-Pol fusion protein (180 kDa). The icosahedral L-A capsid is formed by 120 copies of Gag and has architecture similar to that seen in the reovirus, blue tongue virus and rice dwarf virus inner protein shells. Gag chemically removes the m7GMP caps from host cellular mRNAs. Previously we identified a trench on the outer surface of Gag that included His154, to which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 50 publications
0
42
0
Order By: Relevance
“…In the trench, Tyr150, Asp152, Tyr452, and Tyr538 are located close to the bound m 7 GDP, suggesting their involvement in cap recognition (23). Mutagenesis studies indicate that these residues are crucial for decapping activity.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In the trench, Tyr150, Asp152, Tyr452, and Tyr538 are located close to the bound m 7 GDP, suggesting their involvement in cap recognition (23). Mutagenesis studies indicate that these residues are crucial for decapping activity.…”
Section: Discussionmentioning
confidence: 97%
“…Crystallographic studies of the L-A virion have identified a trench on the outer surface of Gag that includes His154 (22,23). L-A transcripts are made inside the virion and presumably released to the cytoplasm through one of the pores located at the icosahedral 5-fold symmetric axes (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These different roles are directly reflected in the distinct features of the particle surfaces. PcV and L-A CP outer surfaces are highly corrugated, and Gag has a decapping activity (66). It is plausible that PcV CP, in addition to its structural role, might also have enzymatic activity, like L-A Gag.…”
Section: Discussionmentioning
confidence: 99%